2007
DOI: 10.1300/j484v12n03_07
|View full text |Cite
|
Sign up to set email alerts
|

Apical Shoot Harvest Affects Growth and Apical Shoot and Fruit Yields of Pumpkin

Abstract: Apical shoots and fruit of pumpkin (Cucurbita maxima Duch. Ex. Lam.) are edible. A strategy for harvesting apical shoots requires to be developed while sustaining reasonable fruit yields. Field trials were conducted over three years to investigate effects of harvesting 30-or 60-cm long apical shoots at 1-week intervals at population densities of 5,000, 10,000 and 15,000 plants·ha Ϫ1 , or 30-cm long apical shoots at 1-, 1½-, and 2-week intervals in plants sown in late March, mid-April and early May on growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The quality of young leaves of okra as a vegetable decreases with age as the fibre content increases (Olasantan 1988;Schippers 2000). The leaves of the uppermost primary branches are usually smaller and younger and are less fibrous and more succulent than those of the older, lower branches, and are often found to be the most prized and valued by consumers as a vegetable in terms of size, softness, palatability, and nutritional values, as has also been found for sweet potato (Dahniya et al 1985) and pumpkin (Olasantan 2007). Hamm & Charrier (1997) and Schippers (2000) reported that young leaves of okra contain 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The quality of young leaves of okra as a vegetable decreases with age as the fibre content increases (Olasantan 1988;Schippers 2000). The leaves of the uppermost primary branches are usually smaller and younger and are less fibrous and more succulent than those of the older, lower branches, and are often found to be the most prized and valued by consumers as a vegetable in terms of size, softness, palatability, and nutritional values, as has also been found for sweet potato (Dahniya et al 1985) and pumpkin (Olasantan 2007). Hamm & Charrier (1997) and Schippers (2000) reported that young leaves of okra contain 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The crop prefers areas of medium rainfall and does not grow well under very wet conditions. Pumpkin may be useful in biological weed and erosion control in tropical agriculture (Olasantan, 2007). Apical shoots and fruits of pumpkin are edible by humans and some livestock, and they are a good source of protein, vitamins and minerals (Purseglove, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…On plants experienced pruning, there was no addition on number of primary branchs but the stems left keep growing and become long. This was due to the improvement in light interception that possibly resulted in an improvement in vegetative development (Olasantan, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in the number of flowers on plants experienced pruning could be due to some factors. These include reduction in the numbers of secondary branches and leaves and consequently the photosynthetic area of the treated plants and the amount of assimilate available for developing flowers (Olasantan, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation